Cytotoxicity of melittin and apamin in human hepatic L02 and HepG2 cells in vitro. (24th October 2013) - Zhou, Jinhui; Qi, Yitao; Diao, Qingyun; Wu, Liming; Du, Xia; Li, Yi; Sun, Liping
Abstract: The aim of this study is to investigate whether melittin and apamin exhibit any effect on human hepatic cells (L02 cells) and hepatocellular carcinoma cells (HepG2) growth through apoptosis. The results did not show any cytotoxic effect on the L02 cells but did show a synergistic effect of apamin on liver injury. Moreover, melittin and apamin could inhibit the growth of HepG2 cells in a dose-/time-dependent manner and initiate markedly early apoptosis of HepG2 cells. The results of this study showed melittin and apamin have potential as new therapy of liver cancer.